2012
DOI: 10.1007/s11258-012-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of Iberian canopy tree species in relation to wood density, shade tolerance and climate

Abstract: Tree architecture has important consequences for tree performance as it determines resource capture, mechanical stability and dominance over competitors. We analyzed architectural relationships between stem and crown dimensions for 13 dominant Iberian canopy tree species belonging to the Pinaceae (six Pinus species) and Fagaceae (six Quercus species and Fagus sylvatica) and related these architectural traits to wood density, shade tolerance and climatic factors. Fagaceae had, compared with Pinaceae, denser woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
4
12

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 41 publications
4
60
4
12
Order By: Relevance
“…In experimental trials with seedlings, Scots pine was able to grow in low light conditions (Gaudio et al, 2011) due to increased total carotenoid concentration and higher ratios of chlorophyll in response to shade than Maritime pine (Sánchez-Gómez et al, 2006). Although the two studied species are rather similar in many traits, the combination of higher crown plasticity in Maritime pine (Vizcaíno-Palomar et al, 2016), slight differences in shade tolerance between species (Poorter et al, 2012), and the higher physiological plasticity of Scots pine (Gaudio et al, 2011;Sánchez-Gómez et al, 2006) allow both species to develop a multi-layered vertical structure and complementary crown architectures when mixed. Thus, intercepted light can also be used more efficiently, suggesting that light-related interactions may contribute to the mixing effect on stand productivity.…”
Section: Ecological Explanation Of the Mixing Effects On Productivitymentioning
confidence: 95%
See 1 more Smart Citation
“…In experimental trials with seedlings, Scots pine was able to grow in low light conditions (Gaudio et al, 2011) due to increased total carotenoid concentration and higher ratios of chlorophyll in response to shade than Maritime pine (Sánchez-Gómez et al, 2006). Although the two studied species are rather similar in many traits, the combination of higher crown plasticity in Maritime pine (Vizcaíno-Palomar et al, 2016), slight differences in shade tolerance between species (Poorter et al, 2012), and the higher physiological plasticity of Scots pine (Gaudio et al, 2011;Sánchez-Gómez et al, 2006) allow both species to develop a multi-layered vertical structure and complementary crown architectures when mixed. Thus, intercepted light can also be used more efficiently, suggesting that light-related interactions may contribute to the mixing effect on stand productivity.…”
Section: Ecological Explanation Of the Mixing Effects On Productivitymentioning
confidence: 95%
“…Riofrío et al, (2017b) identified large-scale positive interactions between these species when they coexist in mixtures, and suggested that light competition is the main driver limiting growth. These species show similar crown architecture (Poorter et al, 2012) and slight differences in shade tolerance (Gaudio et al, 2011;Sánchez-Gómez et al, 2006), thus slight or null mixing effects could be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Umbila presented lowest basic density (0.636 g cm −3 ) and Jambire the highest (0.841 g cm −3 ). Variation among species in the density of their wood is closely related to variation in light demand [71,72]. Miombo species are semi-light demanding Geldenhuys and Goldings [60].…”
Section: Basic Densitymentioning
confidence: 99%
“…Tree density distributions, which reflected specific ecological site factors, were more appropriate for occurrence of specific species association (e.g., shade-intolerant species and shade-tolerant species) [42][43][44][45]. In theory, shade-intolerant species tend to occur at sparse tree stands, while shade-tolerant species tend to occur at dense tree stands.…”
Section: Motivationmentioning
confidence: 99%
“…Identifying tree-density patterns will be used to simplify species association in a given area where there was no recent disturbance. This hypothesis was based on assumptions that shade tolerance was related to variations in tree architectural parameters, such as stem and crown dimensions [42][43][44][45], and species life history traits (e.g., different seedling time between oaks and pines) and environmental conditions (e.g., topographic and climatic conditions), which constrained species regenerations, resulting in different species dominances (pine dominance and oak-pine codominance) in stands with different tree densities [64,65].…”
Section: Motivationmentioning
confidence: 99%